(untitled) (Islamic Sciences Journal, 2023)
The research deals with the authentication and study of the narration of the two ministers of the Messenger of Allaah –peace and blessing be upon him-, Abū Bakr Al-Ṣiddīq and ‘Umar bin Al-Khattāb –may Allah be pleased with both of them- on who has the right to have the child’s custody, this happened when ‘Umar bin Khattāb divorced his wife Umm ‘Aasim Al-Ansāriyyah, and he attempted to take his child away from her. Abu Bakr then ruled that the right of the child custody belongs to the mother. The research resolves the ways of narration of the hadith from the hadith perspective, and from the analytical perspective, it analyzed the opinions of the four conventional schools of jurisprudence on the issue of child custody. The research findings concluded that the narration could be strengthened with is total ways of narration, hence, becoming “Hassan li ghayrihi” (good due to others), also the hadith has been accepted by the jurists in general. It relies on the extant of application according to them, and that the mother is the most rightful to have child custody so far she has not remarried or left the place where the guardians of the child live, until the child (he/she) is grown up and capable of choosing for him/herself.